SISTEM INFORMASI KEUANGAN BADAN USAHA MILIK DESA (BUMDES) TUNAS MANDIRI DESA NEGARA RATU BERBASIS WEB - Bagus Rahmat Riadi; Machudor Yusman; Yohana Tri Utami (Department of Computer Science, Faculty of Mathematics and Natural Sciences, University of Lampung, 2021)
The financial statements are one of the most important information in assessing the achievements of the company in the past, present and plans for the future. The finansial statements can provide an overview of the company’s financial condition when the report is issued and for those who have an interest in the development and progress of company. The financial reports include the process of recording, calculating, identifying, measuring and preparing economic information in the form of a company’s financial statements that are used for decision making. BUMDes was formed with the aim of improving the village economy by improving services to the community and optimizing village assets to benefit community. BUMDes Tunas Mandiri was founded by the village government of Negara Ratu in 2016. BUMDes Tunas Mandiri is enganged sales, which has two types business, namely selling catfish and kopyor ice. BUMDes Tunas Mandiri conducts financial management is still done manually. BUMDes Tunas Mandiri’s financial information system has been developed by providing features that meet the financial managements needs of BUMDes Tunas Mandiri. The features of this financial information system consist of account management, transactions, journals, trial balances, adjusting journals, ledgers, balance reports, profit and loss reports and changes in capital reports.